Pencils and Pixels: Drawing and Digital Media in Archaeological Field Recording. (17th February 2018) - Morgan, Colleen; Wright, Holly
ABSTRACT: Within the context of a growing emphasis on digital recording, what is the place of analog drawing in archaeological fieldwork? In this article, we situate the increased application of digital drawing methods by providing several historical examples of archaeological field drawing in British archaeology to demonstrate the connection between understanding the archaeological record and illustration. Given this background of analog archaeological recording, we then explore the current state of archaeological field drawing and the affordances of digital illustration for recording and interpreting the archaeological record, review literature in architecture and design regarding the cognitive function of analog and digital drawing, and discuss the possible future implications of born-digital or paperless archaeology.